2013
DOI: 10.1371/journal.pone.0072039
|View full text |Cite
|
Sign up to set email alerts
|

A Method for 3D Immunostaining and Optical Imaging of the Mouse Brain Demonstrated in Neural Progenitor Cells

Abstract: It is important to understand changes in cell distribution that occur as a part of disease progression. This is typically achieved using standard sectioning and immunostaining, however, many structures and cell distribution patterns are not readily appreciated in two-dimensions, including the distribution of neural stem and progenitor cells in the mouse forebrain. Three-dimensional immunostaining in the mouse brain has been hampered by poor penetration. For this reason, we have developed a method that allows f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
42
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(43 citation statements)
references
References 26 publications
(39 reference statements)
1
42
0
Order By: Relevance
“…A recent interest in tissue clearing methods have resulted in the development of several new protocols, all promising to deliver high quality 3D reconstructions of nervous system tissue [1][2][3][4][5][6][7][8][9] .…”
Section: Introductionmentioning
confidence: 99%
“…A recent interest in tissue clearing methods have resulted in the development of several new protocols, all promising to deliver high quality 3D reconstructions of nervous system tissue [1][2][3][4][5][6][7][8][9] .…”
Section: Introductionmentioning
confidence: 99%
“…In vitro molecular imaging of cells and tissues in 2D or 3D space (15)(16)(17) could strongly benefit from the broader spectral imaging window extending into NIR-II, adding more colors and increased multiplexing capability, accompanied by the advantages of increased penetration depth and reduced tissue endogenous autofluorescence levels afforded by molecular NIR-II probes (12,18,19). The increased photon penetration depth allows for visualization of deeper physiological structures, opening the possibility of layer-by-layer fluorescence imaging for 3D molecular imaging using simple one-photon techniques (9,20,21).…”
mentioning
confidence: 99%
“…However, our preliminary results (data not shown) suggest that the enhancement of antibody penetration into thick tissue sections by antibody incubation at 37C were dependent on intense chemical or physical pretreatment to loosen tissue structures. This could explain the controversial results of previous studies (8,14,15) in which antibody incubation at 37C without tissue loosening were shown to have little or no ability to increase antibody diffusion.…”
Section: Resultsmentioning
confidence: 84%
“…One possible mechanism for this effect could be that the higher mobility of antibody during incubation at 37C promotes antibody penetration across the section depth (14), and enhancement of interactions between flexible antigen epitopes and highly mobile antibodies at 37C improves immunolabeling sensitivity (15) and specificity. However, our preliminary results (data not shown) suggest that the enhancement of antibody penetration into thick tissue sections by antibody incubation at 37C were dependent on intense chemical or physical pretreatment to loosen tissue structures.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation